Peran Pondok Pesantren dalam Membentuk Karakter Bangsa Santri di Era Disrupsi - Pasmah Chandra (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Character education has become a phenomenon and an interesting discussion since the last few years. To make matters worse, many educational figures have discussed and conducted research on character education, by connecting character education with the role of educators or educational institutions themselves. Likewise, seeing the role of Islamic boarding schools in character education in the era of disruption. So far the existing studies have not explicitly discussed the process of shaping the character of the nation by Islamic boarding schools. This study aims to complement the previous studies with the aim; first, to determine the role of character education in the students of the Manna Al-Quraniyah Islamic Boarding School. Second, knowing the factors inhibiting and supporting the implementation of character education in the Al-Quraniyah Manna Islamic boarding school students. This type of research is field research with a qualitative approach. The results of the research are as follows: first, the role of the Islamic boarding school in shaping the character of the students can be seen in the implementation of character education at the Al-Quraniyah Manna Islamic boarding school which is carried out through the material taught in the Islamic boarding school then through these materials the students are able to practice it correctly. The implementation of character education is also carried out through the example of kyai, dormitory caregivers, teachers who interact with them, especially those in the boarding school environment. The biggest source of character education implementation comes from the Islamic boarding school program/activity. For example, local content and extracurricular activities. Second, the inhibiting and supporting factors for the implementation of character education consist of internal factors (lack of infrastructure, lack of teaching staff) and external factors (the influence of technological developments).